Methane hydrate formation in a water-continuous vertical flow loop with xanthan gum. (1st April 2020) - Fu, Weiqi; Wang, Zhiyuan; Zhang, Jianbo; Sun, Baojiang
Abstract: Hydrate phase transition in drilling fluid is a non-ignorable problem for developing deep-water oil, natural gas and natural gas hydrate resources. Once gas hydrates form during drilling, it will increase the difficulty of wellbore pressure management and flow assurance, which enlarges the risk of hydrate blockage and causes serious property damage and casualties. Methane hydrate formation experiments are conducted in xanthan gum (XG) aqueous solution to mimic the drilling fluid flowing condition in a vertical flow loop. The experiments reveal that the hydrate formation process is a mass transfer process and experiences four different hydrate formation periods, because of the kinetics formation and slough of hydrate shells. The subcooling temperature has a weaker impact on the hydrate formation than the flow velocity and XG. The increase of flow velocity can enhance the hydrate formation rate in drilling fluid but the increase of XG concentration can inhibit the hydrate formation. The influence mechanisms of hydrate shell kinetic slough, flow velocity and XG concentration on hydrate formation are analyzed and discussed in detail. We built a mass-transfer hydrate formation model based on the mechanism of methane molecule diffusing from gas phase to liquid phase. The empirical overall mass transfer coefficient is introduced involving the influence of hydrate shell kinetic slough, flow velocity and XG concentration. In model validation, the maximum discrepancy of the developed model decreases from 146.85% to 11.03% after using the overall mass transfer coefficient.